I was trying to evaluate the following integral, $$I=\int_\limits {-\infty}^{\infty} \dfrac{\sin(x)}{\sinh(x)}\,dx$$ but had no success. I first expanded the the hyperbolic sine: $$I=2\int_\limits {-\infty}^{\infty} \dfrac{\sin(x)}{e^{x}-e^{-x}}\,dx=2\Im \int_\limits {-\infty}^{\infty} \dfrac{e^{ix}}{e^{x}-e^{-x}}\,dx$$ I then substituted $u=e^x$, $$I=2\Im\int_\limits {0}^{\infty} \dfrac{u^i}{u^2-1}\,du$$ Now, I'm not really sure what to do. Also, after exchanging the $\Im$ with the integral seemed to create a non-integrable singularity at $u=1$. When can you not do that?

  • $\begingroup$ You might have some luck with residue calculus, though I haven't tried. $\endgroup$ – Tob Ernack Nov 30 '17 at 3:07
  • $\begingroup$ wolframalpha.com/input/… $\endgroup$ – user210229 Nov 30 '17 at 3:15
  • $\begingroup$ math.stackexchange.com/questions/2529614/… $\endgroup$ – Guy Fsone Nov 30 '17 at 4:40
  • $\begingroup$ While the OP's integral form is a little off at the end, I believe we can say that the integral is $$\Im\int_0^{\infty}\frac{x^i-x^{-i}}{x^2-1}dx$$ $\endgroup$ – Brevan Ellefsen Dec 13 '17 at 8:02

\begin{align} \int_0^\infty\dfrac{\sin x}{\sinh x}dx &= \int_0^\infty\dfrac{2\sin x}{e^{x}-e^{-x}}dx \\ &= \int_0^\infty\dfrac{2e^{-x}\sin x}{1-e^{-2x}}dx \\ &= \int_0^\infty2e^{-x}\sin x\sum_{n\geq0}e^{-2nx} \\ &= \sum_{n\geq0}2\int_0^\infty e^{-(2n+1)x}\sin x \\ &= \sum_{n\geq0}\dfrac{2}{1+(2n+1)^2} \\ &= \color{blue}{\dfrac{\pi}{2}\tanh\dfrac{\pi}{2}} \end{align} where $$\tanh z=2z\left(\dfrac{1}{z^2+(\frac{\pi}{2})^2}+\dfrac{1}{z^2+(\frac{3\pi}{2})^2}+\dfrac{1}{z^2+(\frac{5\pi}{2})^2}+\cdots\right)$$

  • $\begingroup$ +1, What is a reference for the identity used in the last step? $\endgroup$ – Tob Ernack Nov 30 '17 at 3:52
  • $\begingroup$ It's the expansion of $\tanh z$ which obtain from Mittag-Leffler's expansion theorem (as far as I remember from complex). $\endgroup$ – Nosrati Nov 30 '17 at 3:55
  • 1
    $\begingroup$ I was doing the work with hypergeometric functions when your answer came. It is so nice that I discarded my junk. $\to +1$. $\endgroup$ – Claude Leibovici Nov 30 '17 at 4:00
  • $\begingroup$ @TobErnack I think the last identity could also be obtained from an exponential-type Fourier series. $\endgroup$ – mickep Nov 30 '17 at 6:37

Here is a solution using something akin to the OP's method. We will show that $$\int_0^\infty \frac{x^a-x^{-a}}{x^2-1}dx = \pi \tan\left(\frac{\pi a}{2}\right)$$
From which the OP's integral is immediate. To do so, we will first evaluate the following integral using complex analysis: $$\int_0^\infty \frac{x^a}{x^2-1}dx$$ Given $-1 < \text{Re}(a) < 1$ with $a \neq 0$, we let $\Gamma$ be the following contour. enter image description here

Note that the integrals on $C_r$ and $C_R$ vanish as $r \to 0^+$ and $R \to \infty$ respectively by standard $ML$ estimates. Due to choosing the logarithm to have a branch cut on the positive real line, the $x^a$ in the numerator affects the integral on the positive real line, giving $$\left(\int_R^{1+r} + \int_{1-r}^r\right)f(z)dz = -e^{2\pi ia}\left(\int_r^{1-r} + \int_{1+r}^R\right)f(z)dz\tag{1}$$ By similar reasoning, we find that $$\int_{S_r^-}f(z)dz = e^{2\pi ia}\int_{S_r^+}f(z)dz \tag{2}$$ The integral of $f$ over $S_r^+$ will simply be $$\int_{S_r^+}f(z)dz = -\pi i \operatorname{Res}(1) = - \pi i \lim_{z \to 1} \frac{x^a}{x+1} = \frac{\pi i}{2} \tag{3}$$ Finally, by the residue theorem, the integral of $f$ on $\Gamma$ will simply be $2\pi i \sum \text{Res}(f)$, giving $$\int_\Gamma f(z)dz = 2\pi i \operatorname{Res}(-1) = 2 \pi i \lim_{z \to -1}\frac{e^{a\mathcal{L}_0(z)}}{x-1} = -\pi i e^{a \pi i}\tag{4}$$ Thus, by combining $(1), (2), (3),$ and $(4)$ above, we get $$ (1-e^{2\pi ia})\left(\int_r^{1-r} + \int_{1+r}^R\right)f(z)dz + (1+e^{2\pi ia})\int_{S_r^+}f(z)dz = \int_{\Gamma}f(z)dz $$ So that $$\int_0^\infty \frac{x^a}{x^2-1} = \left(\int_r^{1-r} + \int_{1+r}^R\right)f(z)dz = \frac{\frac{\pi i}{2}(1+e^{2\pi ia})-\pi i e^{a \pi i}}{1-e^{2\pi ia}} = \frac{\pi}{2}\tan\left(\frac{\pi a}{2}\right)$$ Where the last step follows from rearranging the expression into the complex form of $\tan(z)$. Thus we have $$\begin{align} \int_0^\infty \frac{x^a-x^{-a}}{x^2-1}dx &= \int_0^\infty \frac{x^a}{x^2-1}dx - \int_0^\infty \frac{x^{-a}}{x^2-1}dx \\&=\frac{\pi}{2}\tan\left(\frac{\pi a}{2}\right) - \frac{\pi}{2}\tan\left(\frac{-\pi a}{2}\right) \\&= \pi \tan\left(\frac{\pi a}{2}\right) \end{align}$$ Since $tan(z)$ is an odd function. Thus we immediately get the OP's integral by noting $$\begin{align} I&=\int_{-\infty}^{\infty} \frac{\sin(x)}{\sinh(x)}dx \\&= \frac{1}{i}\int_{-\infty}^\infty\frac{e^{ix}-e^{-ix}}{e^x-e^{-x}}dx \\&= \frac{1}{i}\int_0^\infty\frac{x^i-x^{-i}}{x^2-1}dx \\&= \frac{\pi}{i} \tan\left(\frac{\pi i}{2}\right) \\&= \pi \tanh\left(\frac{\pi}{2}\right) \\&\text{As claimed.} \tag*{$\Box$} \end{align}$$


$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$ \begin{align} &\bbox[10px,#ffd]{% 2\int_{0}^{\infty}{\sin\pars{x} \over \sinh\pars{x}}\,\dd x} = 2\,\Im\int_{0}^{\infty}{\expo{\ic x} - 1 \over \pars{\expo{x} - \expo{-x}}/2}\,\dd x \\[5mm] = &\ 4\,\Im\int_{0}^{\infty}{\expo{-\pars{1 - \ic}x} - \expo{-x} \over 1 - \expo{-2x}}\,\dd x \,\,\,\stackrel{\large\expo{-2x}\ =\ t}{\large =}\,\,\, 4\,\Im\int_{1}^{0}{t^{1/2 - \ic/2} - t^{1/2} \over 1 - t}\, \pars{-\,{\dd t \over 2t}} \\[5mm] = &\ 2\,\Im\bracks{\int_{0}^{1}{1 - t^{-1/2} \over 1 - t}\,\dd t - \int_{0}^{1}{1 - t^{-1/2 - \ic/2} \over 1 - t}\,\dd t} \\[5mm] = &\ 2\,\Im\bracks{\Psi\pars{1 \over 2} - \Psi\pars{{1 \over 2} - {\ic \over 2}}} = -2\,\Im\Psi\pars{{1 \over 2} - {\ic \over 2}} \\[5mm] = &\ -2\,{\Psi\pars{1/2 - \ic/2} - \Psi\pars{1/2 + \ic/2} \over 2\ic} = \ic\braces{\pi\cot\pars{\pi\bracks{{1 \over 2} + {\ic \over 2}}}} \\[5mm] = &\ -\ic\pi\tan\pars{\pi\ic \over 2} = \bbx{\pi\tanh\pars{\pi \over 2}} \end{align}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.